Strategy for Strengthening Business Incubators to Form an Entrepreneurial Spirit in Islamic University - Siregar, Dahrul; Yuslem, Nawir; Nawawi, Zuhrinal M (Univeristas Islam Bandung, 2023)
The purpose of this study is to analyze the strategy in Strengthening Business Incubators to Form an Entrepreneurial Spirit in Islamic Higher Education. This study uses the Analytic Network Process method and the help of Super decision software. The results of the study show that the obstacles encountered in the Business Incubator Strengthening Strategy as forming an entrepreneurial spirit in Islamic Universities in North Sumatra can be divided into two, namely internal and external problems. Internal problems come from regulations, lecturers, digitization and infrastructure, while external problems come from network partners, environment and funding. Based on the results of the research that has been done, regulatory issues are a top priority in the Business Incubator Strengthening Strategy to Form an Entrepreneurial Spirit in Islamic Higher Education in North Sumatra with a score of 0.298.